Agricultural diversification and dietary diversity: A feminist political ecology of the everyday experiences of landless and smallholder households in northern Ghana. Issue 86 (November 2017) - Nyantakyi-Frimpong, Hanson
Abstract: There is an emerging literature suggesting that when smallholder households diversify their agriculture, a wide range of food groups will be available, and consequently, dietary diversity will be improved. The present article brings this literature into critical conversation with research in feminist political ecology. Grounded in five years of repeated fieldwork, the article weaves together 70 in-depth interviews, and dietary as well as farm production diversity data from 30 households in northern Ghana. This dataset is analyzed by considering not only the diversity of farming systems, but also household headship, including male-headed, de facto female-headed, and de jure female-headed. Among other findings, the paper suggests that dietary diversity scores are lowest for households who have lost their farmlands to on-going land grabbing in Ghana. Furthermore, the paper suggests that while agricultural diversification is essential, it is not sufficient in itself to address nutritional challenges confronting smallholder households. In the contested and political arena of the household, the gendered politics of access to food can deeply shape how agricultural diversification contributes to dietary diversity. Overall, I do not wish to conclude that there are no benefits of increasing the diversity of farm production. Rather, I wish to stress that farm production diversity might not be the best or only strategy to improving dietary diversity among rural households. Through this case study, I also contribute to emerging research in new feminist political ecologies by demonstrating how the intersection of gender, seniority, marital status, and sexual politics shapes resource access and control.